2010
DOI: 10.3844/ajassp.2010.954.961
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oil Contamination on Geotechnical Properties of Basaltic Residual Soil

Abstract: Problem statement: Oil contamination due to accidental spillage or leakage brings hefty damage to the environments. It percolates steadily into subsurface environments and contaminates the soil and water system. Hydrocarbon contamination has not just affected the quality of the soil but will also alter the physical properties of oil-contaminated soil. Approach: This study presented the geotechnical properties of oil-contaminated soils as well as uncontaminated soils for comparison. Testing progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 15 publications
5
31
1
3
Order By: Relevance
“…It can be generally discussed herein that hydrocarbon contaminations reduces hydraulic conductivity of soils (Akinwumi et al 2014a;Akinwumi et al 2014b;Al-Sanad et al 1995;Budhu et al 1991;Cook et al 1992;Foreman and Daniel 1986;Khamehchiyan et al 2007;Meegoda and Rajapakse 1993;Puri 2000;Puri et al 1994;Rahman et al 2010;Shin and Das 2000;Siang et al 2014;Silvestri et al 1997;Singh et al 2008;Singh et al 2009;Tuncan and Pamukcu 1992;Uppot and Stephenson 1989). Totally, deposition of hydrocarbon compounds into soil pores, as influential elements governing hydraulic conductivity of soils, considerably decreases soil permeability.…”
Section: Hydraulic Conductivitymentioning
confidence: 98%
See 3 more Smart Citations
“…It can be generally discussed herein that hydrocarbon contaminations reduces hydraulic conductivity of soils (Akinwumi et al 2014a;Akinwumi et al 2014b;Al-Sanad et al 1995;Budhu et al 1991;Cook et al 1992;Foreman and Daniel 1986;Khamehchiyan et al 2007;Meegoda and Rajapakse 1993;Puri 2000;Puri et al 1994;Rahman et al 2010;Shin and Das 2000;Siang et al 2014;Silvestri et al 1997;Singh et al 2008;Singh et al 2009;Tuncan and Pamukcu 1992;Uppot and Stephenson 1989). Totally, deposition of hydrocarbon compounds into soil pores, as influential elements governing hydraulic conductivity of soils, considerably decreases soil permeability.…”
Section: Hydraulic Conductivitymentioning
confidence: 98%
“…One of the important characteristics of fine-grained soils contaminated by hydrocarbon compounds has been Atterberg limits. In a more general sense and based on an overall look at some relevant research (Akinwumi et al 2014a;Akinwumi et al 2014b;Alhassan and Fagge 2013;Jia et al 2010;Kermani and Ebadi 2012;Khamehchiyan et al 2007;Khosravi et al 2013;Nazir 2011;Pusadkar and Bharambe 2014;Rahman et al 2010;Solly et al 2015;Srivastava and Pandey 1998;Ukpong and Umoh 2015;Walia et al 2013), the authors are not able to find a comprehensive trend describing the effects of hydrocarbons on these limits. To elucidate this fact, the authors have approximately accumulated all the data provided in the literature regarding both LL and PI of hydrocarbon-contaminated soils in Fig.…”
Section: Atterberg Limitsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Rahman, Hamzah, Taha, Ithnain, and Ahmad (2010) showed that contaminates in OCS would have lower Maximum Dry Density and optimum water content if compared with uncontaminated soils, in general, a decreased permeability and kPa. They claim that despite the adverse effects, contaminated residual might be used for geotechnical purposes.…”
Section: Geotechnical Properties Of Oil-contaminated Soilmentioning
confidence: 98%